2019
DOI: 10.13057/biodiv/d200402
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of Tenera × Tenera and Tenera × Pisifera Crosses and D self of oil palm (Elaeis guineensis) parental populations originating from Cameroon

Abstract: Abstract. Budiman LF, Apriyanto A, Pancoro A, Sudarsono S. 2019. Genetic diversity analysis of Tenera × Tenera and Tenera × Pisifera Crosses and D self of oil palm (Elaeis guineensis) parental populations originating from Cameroon. Biodiversitas 20: 937-949. There are three types of oil palm (Elaeis guineensis Jacq.) based on the shell thickness, such as the Dura (D type, with a thick shell), the Pisifera (P type, with no or very thin shell) and the Tenera (T type, with medium shell thickness), respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
4
8
1
1
Order By: Relevance
“…The highest number of alleles (6 alleles per locus) was detected for sMg00016, whereas loci sEg00154, mEgCIR3519 and sMg00179 presented 5 alleles per locus. Similar studies involving the analysis and characterization of microsatellites in oil palm have also detected loci with highly variable number of alleles, as well as the polymorphic information content (2 to 6 alleles per locus, Bakoumé et al, 2011; 3 to 8 alleles per locus, Hama-Ali et al, 2015; 5 to 11 alleles per locus, Budiman et al, 2019). The highest polymorphism information content (PIC) value was detected for the locus sMg00179 (0.7103), while the lowest PIC value of 0.3750 was recorded for the locus sEg00151 with a mean value of 0.5843.…”
Section: 5843mentioning
confidence: 77%
“…The highest number of alleles (6 alleles per locus) was detected for sMg00016, whereas loci sEg00154, mEgCIR3519 and sMg00179 presented 5 alleles per locus. Similar studies involving the analysis and characterization of microsatellites in oil palm have also detected loci with highly variable number of alleles, as well as the polymorphic information content (2 to 6 alleles per locus, Bakoumé et al, 2011; 3 to 8 alleles per locus, Hama-Ali et al, 2015; 5 to 11 alleles per locus, Budiman et al, 2019). The highest polymorphism information content (PIC) value was detected for the locus sMg00179 (0.7103), while the lowest PIC value of 0.3750 was recorded for the locus sEg00151 with a mean value of 0.5843.…”
Section: 5843mentioning
confidence: 77%
“…The SSR markers had been widely used for genetic diversity analysis of perennial estate crops (Ajambang, Sudarsono, Asmono, & Toruan, 2012;Budiman, Apriyanto, Pancoro, & Sudarsono, 2019;Cochard et al, 2009;Larekeng, Maskromo, Purwito, Mattjik, & Sudarsono, 2015;Maskromo, Larekeng, Novarianto, & Sudarsono, 2017;Natawijaya et al, 2019;Tinche, Asmono, Dinarti, & Sudarsono, 2014). SSR loci are co-dominant and are spreaded within the plant genome.…”
Section: Resultsmentioning
confidence: 99%
“…Copyright © 2019 Universitas Brawijaya Many studies have shown the presence of a high allelic variation among different plant populations (Illahi, Wiendi, & Sudarsono, 2016;Larekeng, Purwito, Mattjik, & Sudarsono, 2018;Oktavia, Kuswanhadi, Dinarty, Widodo, & Sudarsono, 2017;Purwoko, Cartealy, Tajuddin, Dinarti, & Sudarsono, 2019;Sulistiyorini, Rubiyo, & Sudarsono, 2018). The SSR markers are used as powerful tools for supporting plant breeding of many perennial crops, including oil palm (Ajambang, Sudarsono, Asmono, & Toruan, 2012;Budiman, Apriyanto, Pancoro, & Sudarsono, 2019;Larekeng, Maskromo, Purwito, Matjik, & Sudarsono, 2015;Maskromo, Larekeng, Novarianto, & Sudarsono, 2017;Natawijaya et al, 2019;Tinche, Asmono, Dinarti, & Sudarsono, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of some DNA-based molecular markers to study the population genetics of oil palm has been reported by some oil palm researchers (Bakoumé et al 2014; Barcelos et al 2002;Budiman et al 2019;Hayati et al 2004;Ithnin et al 2017;Natawijaya et al 2018;Okoye et al 2016). Among molecular markers, microsatellite or simple sequence repeats (SSRs) as codominant and multiallelic markers have been widely used to estimate the oil palm genetic diversity.…”
Section: B I O D I V E R S I Tmentioning
confidence: 99%